‘Shit Happens’: The Selling of Risk in Extreme Sport - Palmer, Catherine (The Australian journal of anthropology, 2002)
This article details the particular commodification of those high-risk, highadrenalin activities known collectively as ‘extreme sports’. A variety of commercial operators now offer relative sporting neophytes the chance to take part in mountaineering, snow boarding or canyonning adventures that are billed as being ‘high thrill, low risk’. It is the way in which the risk and danger involved in these activities is discursively managed that is of particular interest for this article. The argument developed is that in selling extremity through a range of primarily tourist-oriented commercial avenues, the very real prospect of death and injury has been stripped from the activity itself. To elaborate this position, this article draws on several sporting disasters, including the much publicised, ill-fated ascent of Mount Everest in 1996, and the Interlaken canyonning disaster of 1999, as well as the burgeoning literary and media genre—the made-for-Hollywood ‘adventure saga’.